(3aGYdjI ESJQGJjLjI bGFeI Ydi GdeONd GdeYQai dJfejI egGQGJ GdJPhb GdCOHi hGdGJLGg fMh GdfUhU GdGOHjI dOi WdGH GdeQMdI GdKGfhjI(B/s - (3Cejf eMeO eMeO CHh HcQ s ([(3O(B.(3e(B]:s [(3O(B.(3f(B](3,s, 2009)
(3edNU HGddZJjf GdYQHjI hGdGfLdjRjI (B.s
(3GdeQGLY ef U (B200-218.s
(3OQLI GdeGLSJjQ ai GdJQHjI s
(3eYgO GdOQGSGJ hGdHMhK GdJQHhjI (B: (3bSe GdefGgL hWQb GdJOQjS , LGeYI GdbGgQI (B.s
Keywords: (3egGQGJ GdJPhb GdCOHi (B.s